Potensi Ekstrak Daun Paku Resam (Gleichenia linearis Burm.) Sebagai Bioherbisida Pengendali Gulma Rumput Grinting (Cynodon dactylon (L.) Pers) - ., Enny Tri Septiani, Mukarlina (Jurnal Protobiont, 2017)
Gleichenia linearis is a wide leaf weed which contains chemical compound such as flavonoid, allelochemical, triterpenoid, saponin, tannin, alkaloid and steroid that can inhibit the growth of other plants as a bioherbicide. This study aims to determine the concentration of G. linearis leaf extract on germination and growth of seedling weed Cynodon dactylon. This study was conducted in a laboratory and a screen house of Biology Department of Mathematics and Natural Science Faculty in Chemical and Soil Fertility Laboratory of Agriculture Faculty and in Wood Technology Laboratory of Forestry Faculty of University of Tanjungpura Pontianak from September to November 2016. The study employed completely randomized design with 5 replicates consisting control, 0,1; 0,2 and 0,3 gr/ml (germination) than control, 0,1 and 0,2 gr/ml (growt). The research findings showed that effective concentration that can inhibit germination of weed C. dactylon is 0,3 gr/ml concentration and inhibit the growth of other plants is 0,2 gr/ml concentration.